Information Technology for Small Business Managing the Digital Enterprise - Passerini, Katia; El Tarabishy, Ayman; Patten, Karen; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
Information Technology for Small Business: Managing the Digital Enterprise provides an overview of how small and medium business enterprises (SMEs) can use flexibility, agility, and anticipation strategies to better utilize information technology and knowledge management. Because small and medium businesses tend to be late technology adopters, they could miss versatile and strategic workforce advantages that enable them to achieve higher efficiency and effectiveness through technology. This book shows these SMEs new technology trends that can transform the nature of their operations both in an evolutionary business path and through revolutionary opportunities. Information Technology for Small Business: Managing the Digital Enterprise applied correctly to small and medium business can be used as a strategic tool to reach growth and profit goals for the SMEs competing in a very dynamic and global marketplace. Examples include: identifying ways that IT can be used to develop strong relationships with customers and suppliers, and how to select the best technologies for business needs. Information Technology for Small Business: Managing the Digital Enterprise targets SME owners, educators, and practitioners working in the related fields of management, IT, IS, and CS-related disciplines. Advanced-level students and policy makers focusing on SMEs will also find this book valuable in terms of main concepts for discussion.
Introduction -- SMEs and Information Technologies in the Broadband Economy -- SME Opportunities with Broadband-Driven Information Technologies: Supporting SME Business Needs -- The Changing Nature of (3z(BWorkspace(3y (Band (3z(BWorkplace:(3y (BWhat It Means for SMEs -- Existing and Emerging Information Technologies for SMEs -- Selecting, Planning, and Deploying SME Broadband-based Information Services, Applications, and Technologies -- Managing & Maintaining SMEs Information Services and Applications -- Cases on SMEs Digital Innovations -- The IT Entrepreneur in SMEs.s
Keywords: Economics; Information Systems; Management information systems; Economics/Management Science; Innovation/Technology Management; Information Systems Applications (incl. Internet).; Management of Computing and Information Systems; Business Information Systems